Humoral and Cellular Immune Responses Against Severe Acute Respiratory Syndrome Coronavirus 2 Variants and Human Coronaviruses After Single BNT162b2 Vaccination. (16th June 2021) - Stankov, Metodi V; Cossmann, Anne; Bonifacius, Agnes; Dopfer-Jablonka, Alexandra; Ramos, Gema Morillas; Gödecke, Nina; Scharff, Anna Zychlinsky; Happle, Christine; Boeck, Anna-Lena; Tran, Anh Thu; Pink, Isabell; Hoeper, Marius M; et al.
Abstract: Background: Vaccine-induced neutralizing antibodies are key in combating the coronavirus disease 2019 (COVID-19) pandemic. However, delays of boost immunization due to limited availability of vaccines may leave individuals vulnerable to infection and prolonged or severe disease courses. The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOC)—B.1.1.7 (United Kingdom), B.1.351 (South Africa), and P.1 (Brazil)—may exacerbate this issue, as the latter two are able to evade control by antibodies. Methods: We assessed humoral and T-cell responses against SARS-CoV-2 wild-type (WT), VOC, and endemic human coronaviruses (hCoVs) that were induced after single and double vaccination with BNT162b2. Results: Despite readily detectable immunoglobulin G (IgG) against the receptor-binding domain of the SARS-CoV-2 S protein at day 14 after a single vaccination, inhibition of SARS-CoV-2 S-driven host cell entry was weak and particularly low for the B.1.351 variant. Frequencies of SARS-CoV-2 WT and VOC-specific T cells were low in many vaccinees after application of a single dose and influenced by immunity against endemic hCoV. The second vaccination significantly boosted T-cell frequencies reactive for WT and B.1.1.7 and B.1.351 variants. Conclusions: These results call into question whether neutralizing antibodies significantly contribute to protection against COVID-19 upon single vaccination and suggest that cellular immunity is central for the early defenses against COVID-19. Abstract : We assessed single vaccine shot–induced B- and T-cell responses against SARS-CoV-2, variants of concern, and human coronaviruses to determine protection against COVID-19. Our results provide important information about surrogates of protection, test result interpretation, and clinical decision-making.